Strengthening The Culinary Creative Economy Cluster in Kampung Kue MSMEs - Ayundha Evanthi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
The transformation of Kampung Kue into a culinary tourism area is reinforced by the industrial cluster approach, where the geographical grouping of cake producers creates production efficiency, ease of access to raw materials, information exchange, and product innovation. This cluster approach is considered effective in strengthening the regional economy and increasing the competitiveness of MSMEs. The role of universities, particularly the Community Service Team of UPN Veteran Jawa Timur, has also encouraged the capacity building of MSMEs through socialization and discussions related to the creative economy. The article also emphasizes that the creative economy, especially the culinary sub-sector, provides added value through flavor innovation, packaging development, branding, and digital promotion—which then expands market reach. The synergy between the production cluster and the creative economy has made Kampung Kue not only a culinary hub but also a local cultural icon and a model for inclusive community-based economic development. These efforts are expected to continue improving community welfare through SME strengthening, product innovation, and culinary tourism promotion.